The Role of Leadership Style and Social Work Environment Toward Employee Engagementat Bank Mandiri Ujung Menteng Branch : - Boris Lukman; Budi Prijono (Perbanas Institute, 2022)
This study aims to analyze the role of leadership style and social work environment on Employee Engagementat Bank Mandiri Ujung Menteng branch. In this study, there are two independent variables, namely leadership style and social work environment to test their role on the dependent variable, namely Keterlibatan Karyawan. The population of this research is the employees of Bank Mandiri Ujung Menteng branch, totaling 35 people. Sampling with saturated sampling method, so that the entire population is used as a sample of 35 respondents, . The data collection technique was using a questionnaire with SPSS version 25. The analytical tool used was multiple linear regression test. The results showed that: Leadership style has a negative and significant effect on Employee Engagement, while the social work environment has no significant effect on Employee Engagement. The results of the test of the coefficient of determination between the variables of leadership style and social work environment on Employee Engagement are 53.6%, and there are other factors of 46.4% influenced by other variables outside of this study. So it is recommended for further researchers to add independent variables that have not been studied. And the application of leadership style at Bank Mandiri Ujung Menteng branch with achievement-oriented leadership style.